2022
DOI: 10.1039/d1en00680k
|View full text |Cite
|
Sign up to set email alerts
|

Determination of metallic nanoparticles in biological samples by single particle ICP-MS: a systematic review from sample collection to analysis

Abstract: A systematic review of the use of single particle ICP-MS to analyse engineered nanomaterials in biological samples has highlighted that efforts have focused on a select few compositions and there is a lack of information for some important tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 147 publications
(195 reference statements)
0
23
0
Order By: Relevance
“…54 The nanoparticles from biological matrices have been successfully extracted from biological matrices using acids, alkalis, or enzymes, as reported in the literature. 55 However, standard protocols cannot be applied to nanoparticles in different biological matrices. Reliable protocols for spICP-MS sample preparation are urgently needed, for example, the development of certified reference materials for nanoparticles in biological matrices for method validation.…”
Section: Recent Advances In Icp-ms-based Methodologymentioning
confidence: 99%
“…54 The nanoparticles from biological matrices have been successfully extracted from biological matrices using acids, alkalis, or enzymes, as reported in the literature. 55 However, standard protocols cannot be applied to nanoparticles in different biological matrices. Reliable protocols for spICP-MS sample preparation are urgently needed, for example, the development of certified reference materials for nanoparticles in biological matrices for method validation.…”
Section: Recent Advances In Icp-ms-based Methodologymentioning
confidence: 99%
“…A critical and comprehensive review of sp-ICP-MS (301 references) discussed 39 the evolution and principles of the technique, together with methods for the study of NPs in numerous sample matrices including soils and plants. Another review (159 references) focussed 172 specifically on metallic NPs in biological samples. Both sets of authors identified the paucity of properly validated standardised methods and the lack of suitable NP CRMs as major factors hampering progress in the field.…”
Section: Analysis Of Soils Plants and Related Materialsmentioning
confidence: 99%
“…After vortexing for 5 s, the solutions were made up to 5.0 mL and analysed. In reviewing the determination of metallic NPs in biological samples by spICP-MS, Laycock et al 11 found that alkaline-based extraction methods have been quite widely applied, particularly in the preparation of animal tissue samples. The review contains a useful summary table in which papers are grouped by sample preparation method.…”
Section: Sample Collection and Preparationmentioning
confidence: 99%